Is bike sharing competitor, relief or supplement to public transport?. - Leth, Ulrich; Brezina, Tadej; Ludwig, Bertram; Birett, Christina (My University, 2017)
Der Beitrag geht, am Beispiel von "CityBike Wien - CBW", der Frage nach, ob öffentliche Fahrradverleihsysteme eher als Ergänzung oder als Konkurrenz zum öffentlichen Stadtverkehr gesehen werden können. Hierzu wurden die CBW-Reisedaten eines Jahres analysiert und eine Befragung unter 1389 CBW-Nutzern durchgeführt.

In many cities the growing popularity of bicycle-sharing schemes has added additional options to the transport regime. A significant amount of research has been stipulated by data recorded from lending and returning bicycles at geographically diverse stations. In this contribution, focus will be laid on the relationship that the bike-sharing system of the City of Vienna (CityBike Wien - CBW) has with its well developed public transport system. Does bike-sharing serve as competitor, relief or supplement? By surveying the total CBW trip data of 2015 - about 1 million records - we approach to answer this question. We cleanse and route all bicycle trips and compare them with routed alternative public transport trips in terms of travel time ratios. In interviews of 1389 CBW users conducted in July and September/October of 2016, we ask about the purpose of their trip, the position of the CBW as part of their door-to-door trip, the role of CBW as substitute for other means of transport and the reasons for this substitution. The age group that has the highest number of users among CBW and the shares of tourists/visitors and locals using CBW is identified. Identifying the top 10 of trips from the cleansed dataset and mapping them emphasizes the role that we identify for Vienna's bike-sharing system in the inner city: A supplement to public transport.
Keywords: Öffentlicher Verkehr; Fahrradverleih; Fahrrad; Gemeinschaftsnutzung; Verkehrsmittelwahl; Bikesharing